2015
DOI: 10.1111/jace.13769
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Ion Conduction in Bulk and Grain Boundaries of Nominally Donor‐Doped Lead Zirconate Titanate (PZT): A Combined Impedance and Tracer Diffusion Study

Abstract: Oxygen ion conduction in Nd 3+ -doped Pb(Zr x Ti 1 -x )O 3 (PZT) was investigated by impedance spectroscopy and 18 O-tracer diffusion with subsequent secondary ion mass spectrometry (SIMS) analysis. Ion blocking electrodes lead to a second relaxation feature in impedance spectra at temperatures above 600°C. This allowed analysis of ionic and electronic partial conductivities. Between 600°C and 700°C those are in the same order of magnitude (10-4 S/cm) though very differently activated (2.4 eV vs. 1.2 eV for io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…However, it has been shown that p‐type conducting, acceptor‐doped material with surface space charge often exhibits oxygen deficiency toward the surface while n‐type donor doped ceramics often show oxygen enrichment. This is well in line with the results presented in this study . In addition, it can be seen from Figure that the incorporation of the tracer increases with increasing BZT content in the actual bulk region as well.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, it has been shown that p‐type conducting, acceptor‐doped material with surface space charge often exhibits oxygen deficiency toward the surface while n‐type donor doped ceramics often show oxygen enrichment. This is well in line with the results presented in this study . In addition, it can be seen from Figure that the incorporation of the tracer increases with increasing BZT content in the actual bulk region as well.…”
Section: Resultssupporting
confidence: 92%
“…The profiles of BT‐3BZT and BT‐7.5BZT show a much higher 18 O concentration but can also not be evaluated with common diffusion equations. They instead show a similar behavior observed for donor ‐doped PZT . There, an enrichment of oxygen vacancies toward the surface results in a surface space charge layer and leads to a much more extensive exchange of oxygen.…”
Section: Resultsmentioning
confidence: 54%
“…Calculations based on the STO defect chemical data set of [10] also reveal that an increase in the Fe content without changing the net acceptor doping should strongly lower Db*, in complete contrast to the experimental data of co-doped samples (see Figure 11b). Fe 3+ + h + => Fe 4+ as the only hole-trapping reaction cannot explain the strongly temperature-dependent hole conductivity found in PZT without Fe dopants [42]. Moreover, preliminary measurements with Cu 2+ doping (0.25%) revealed even lower Db* values than found for analogous iron doping (0.5%), despite the absence of the iron-based hole trap; (iii) We therefore suggest the existence of additional intrinsic neutral traps T x in PZT which become positively charged by holes according to Tx+h    Thor Tx+2normalh    normalT2normalh…”
Section: Resultsmentioning
confidence: 99%
“…Donor-doped PZT, on the other hand, has a measureable bulk vacancy concentration, probably in the sub-ppm range (0.01–0.1 ppm in our case), and a substantial oxygen vacancy concentration in grain boundaries. The latter is discussed in more detail in [32,42]. …”
Section: Resultsmentioning
confidence: 99%
“…The calculated k p and Qm results and the piezoelectric charge coefficient d 33 (C/N or m/V) are presented in Table . The d 33 decreased with Gd doping from 532 pC/N for x = 0 sample to 419 pC/N for x = 0.02 sample, which is due to the decrease of c/a value and the reduction in oxygen vacancies . The d 33 enhances with the increase of x , reaching a maximum value of 458 pC/N for x = 0.04.…”
Section: Resultsmentioning
confidence: 99%